Physical Appearance Comparison and Body Dissatisfaction in Women Users of Tiktok and Instagram - Apriliani, Ni Made Rutina Rizki; Soetjiningsih, Christiana Hari (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
This research aims to determine the significance of the relationship between physical appearance comparison and body dissatisfaction in female users of TikTok and/or Instagram. Participants were 203 female TikTok and/or Instagram users using purposive sampling techniques. The data collection method used is the Physical Appearance Comparison Scale-Revised (PACS-R) from Schaefer and Thompson (2014) which has been tested for construct validity in Indonesia by Qidwati (2019) and the Body Dissatisfaction Scale (BDS) from Tariq and Ijaz (2015 ) which has been tested for construct validity in Indonesia by Arshuha (2019). The data analysis technique used is the Pearson Product Moment correlation technique. From the results of data analysis, a correlation coefficient (rxy) of 0.548 was obtained with a significance value of 0.000 (p<0.01), which means there is a significant positive relationship between physical appearance comparison and body dissatisfaction in female TikTok and/or Instagram users. This means that a high physical appearance comparison will be followed by high body dissatisfaction, whereas if the physical appearance comparison is low it will be followed by low body dissatisfaction. The implication of this research is that women who use TikTok and/or Instagram need to reduce the behavior of comparing their own appearance with the appearance of others (physical appearance comparison) in order to avoid and not experience body dissatisfaction which can make women feel dissatisfied with their appearance and body shape.Penelitian ini bertujuan untuk mengetahui signifikansi hubungan antara physical appearance comparison dengan body dissatisfaction pada wanita pengguna TikTok dan/atau Instagram. Partisipan berjumlah 203 wanita pengguna TikTok dan/atau Instagram dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan yaitu Physical Appearance Comparison Scale-Revised (PACS-R) dari Schaefer dan Thompson (2014) yang telah di uji validitas konstruk di Indonesia oleh Qidwati (2019) dan Body Dissatisfaction Scale (BDS) dari Tariq dan Ijaz (2015) yang telah di uji validitas konstruk di Indonesia oleh Arshuha (2019). Teknik analisis data yang digunakan adalah teknik korelasi Product Moment Pearson. Dari hasil analisis data diperoleh koefisien korelasi (rxy) 0.548 dengan nilai signifikansi 0.000 (p<0,01) yang artinya ada hubungan positif yang signifikan antara physical appearance comparison dengan body dissatisfaction pada wanita pengguna TikTok dan/atau Instagram. Hal ini bermakna bahwa physical appearance comparison tinggi akan diikuti dengan body dissatisfaction yang tinggi sebaliknya apabila physical appearance comparison rendah maka akan diikuti dengan body dissatisfaction yang rendah. Implikasi dari penelitian ini yaitu wanita yang menggunakan TikTok dan/atau Instagram perlu untuk mengurangi perilaku membandingkan penampilan diri dengan penampilan orang lain (physical appearance comparison) supaya terhindar dan tidak mengalami body dissatisfaction yang dapat membuat wanita merasa tidak puas akan penampilan dan bentuk tubuhnya.